Readings in late antiquity : a sourcebook - Maas, Michael, 1951- (Routledge sourcebooks for the ancient world., 2010)
Late Antiquity (ca. 250-650) witnessed the transition from Classical Antiquity to the Middle Ages in the Mediterranean and Near Eastern worlds. Christianity displaced polytheism over a wide area, offering new definitions of identity and community. The Roman Empire collapsed in Western Europe to be replaced by new ""Germanic"" kingdoms. In the East, Byzantium emerged, while the Persian Empire reached its apogee and collapsed. Arab armies carrying the banner of Islam reshaped the political map and brought the late antique era to a close. This sourcebook illustrates the dramatic politica.